Efficacy and Clinical Applicability of Impar Ganglion Block in the Treatment of Pudendal Neuralgia: A Systematic Review - Joelington Dias Batista; Gabrielly Santos Pereira; Jobson Dias Batista; Ludimila Dias Silva; Josie Resende Torres da Silva; Marcelo Lourenço da Silva (Surgical Techniques Development, 2025)
Background/Objectives: Pudendal neuralgia (PN) is a debilitating chronic pain condition resulting from injury, inflammation, or entrapment of the pudendal nerve. It significantly affects patients’ quality of life and poses challenges to treatment due to its complex etiology. Conventional therapies often provide limited or temporary relief. The impar ganglion block (IGB) has emerged as a potential intervention for managing refractory pelvic pain syndromes. This systematic review aimed to evaluate the clinical efficacy, safety, and applicability of IGB in treating patients with PN. Methods: This systematic review evaluates the efficacy and clinical applicability of IGBs in treating PN. Following PRISMA-P 2020 guidelines, a systematic search was conducted in PubMed/MEDLINE, Embase, LILACS, and Cochrane Library. Eligible studies included RCTs, observational studies, and case series assessing pain reduction and quality of life post-IGB. Non-neuropathic pelvic pain studies were excluded. The ROBVIS tool assessed the risk of bias. Results: Of 306 articles screened, 16 met eligibility criteria. Studies showed that the IGB provides significant pain relief, particularly for refractory cases. Image-guided techniques enhanced precision and reduced complications. Combination therapies with corticosteroids yielded longer-lasting analgesia. However, methodological inconsistencies and varied patient selection limited generalizability. Conclusions: The IGB is a minimally invasive, effective option for managing PN. Further high-quality RCTs are needed to standardize protocols, optimize patient selection, and evaluate long-term efficacy. A multidisciplinary approach remains essential.